Long-term Exon Skipping Studies With 2'-O-Methyl Phosphorothioate Antisense Oligonucleotides in Dystrophic Mouse Models - Christa L Tanganyika-de Winter; Hans Heemskerk; Tatyana G Karnaoukh; Maaike van Putten; Sjef J de Kimpe; Judith van Deutekom; Annemieke Aartsma-Rus (Elsevier, 2012)
Antisense-mediated exon skipping for Duchenne muscular dystrophy (DMD) is currently tested in phase 3 clinical trials. The aim of this approach is to modulate splicing by skipping a specific exon to reframe disrupted dystrophin transcripts, allowing the synthesis of a partly functional dystrophin protein. Studies in animal models allow detailed analysis of the pharmacokinetic and pharmacodynamic profile of antisense oligonucleotides (AONs). Here, we tested the safety and efficacy of subcutaneously administered 2'-O-methyl phosphorothioate AON at 200 mg/kg/week for up to 6 months in mouse models with varying levels of disease severity: mdx mice (mild phenotype) and mdx mice with one utrophin allele (mdx/utrn+/−; more severe phenotype). Long-term treatment was well tolerated and exon skipping and dystrophin restoration confirmed for all animals. Notably, in the more severely affected mdx/utrn+/− mice the therapeutic effect was larger: creatine kinase (CK) levels were more decreased and rotarod running time was more increased. This suggests that the mdx/utrn+/− model may be a more suitable model to test potential therapies than the regular mdx mouse. Our results also indicate that long-term subcutaneous treatment in dystrophic mouse models with these AONs is safe and beneficial.